Oncogenic role of cancer-associated fibroblast secretion in endometrial cancer progression in vitro and in vivo / Kavita S. Subramaniam - Kavita, S. Subramaniam (2016)
Cancer-associated fibroblasts (CAFs) have demonstrated tumor-promoting roles in various cancers, yet their implication in endometrial cancer (EC) has not been fully explored. CAFs and its epithelial counterpart were isolated from human EC tissues using CD90- and CD326-antibodies conjugated magnetic beads, respectively. Isolated cell populations were characterized using morphology assessment, flow cytometry, and real-time PCR. CAFs secretion increased EC cell proliferation (195.3 ± 12.9%) and enhanced motility (134.9 ± 6.5%) while benign endometrial fibroblasts inhibited proliferation (62.4 ± 21.2%) and suppressed motility (15.2 ± 8.2%). Antibody array and ELISA showed higher GRO-α, IL-6, MCP-1, VEGF and RANTES cytokines levels in CAFs, than in benign fibroblast secretion. Of note, interleukin-6 (IL-6) was secreted 4.17-folds greater in CAFs; neutralizing its effect reduced EC proliferation (36.1 ± 4.2%) while treatment of EC cells with IL-6 recombinant protein alone increased cell proliferation. Interestingly, EC cells but not CAFs expressed IL-6 receptors (IL-6R and gp-130). Upon treatment with CAFs secretion, IL-6 receptor signaling was activated as evidenced with increased phosphorylation of Erk, Akt, JAK-3 and STAT-3 proteins. Suppression of these pathways using chemical inhibitors led to reduced CAFs-mediated EC cell proliferation. Further, STAT-3 target genes (TIMP-1, PIM-1, c-Myc, SOCS-3, NFκB1 and NFκB2) were upregulated. c-Myc mRNA level was elevated 138-folds higher in CAFs-treated EC cells and c-Myc knockdown with shRNA reduced EC cell proliferation (52.7 ± 1.8%). Surprisingly, treatment with CAFs secretion did not significantly increase the cell proliferation (64.1 ± 4.7%). To observe whether CAFs modulates EC growth in vivo, epithelial and fibroblast cells were inoculated subcutaneously into nude mice. Fibroblast cells alone and co-injections of benign fibroblast with EC cells showed no induction of tumor growth. However, co-injection of CAFs with EC cells showed increased growth (1166.2 ± 59.3 mm3) compared to EC cells alone (497.6 ± 36.7 mm3). EC cells with iv reduced c-Myc expression grew into smaller tumors (293.9 ± 7.02 mm3) compared to those with high c-Myc level (748.4 ± 8.2 mm3), despite exposure to CAFs (361.9 ± 38.7 mm3). These suggest that CAFs exerts tumor-promoting effects in EC via c-Myc expression both in vitro and in vivo. Subsequent immunohistochemical analysis on human tissue specimens showed high expression of IL-6 receptors, phosphorylated STAT-3 and c-Myc protein in EC (n=9) but not in benign endometrial tissues (n=8). We further tested IL-6 receptors specific inhibitors (raloxifene and bazedoxifene acetate) and PI3K inhibitor (rapamycin) on CAFs-treated EC cells, and observed inhibition of proliferation (44.3 ± 2.6%, 46.2 ± 2.9% and 30.7 ± 12.1%, respectively), with evidence of apoptosis-mediated cell death. Our data shows that CAFs exert a growth-promoting role in EC tumor microenvironment, partly through activation of IL-6 receptors in EC cells to induce expression of c-Myc. Our study provides proof-of-principle evidence that CAFs-mediated IL-6 signaling has a direct role in EC tumorigenesis, which can be employed for novel EC therapeutic utility.